Seroprevalence and Associated Risk Factors of Foot and Mouth Disease in Cattle in West Shewa Zone, Ethiopia - Beyan Ahmed; Lencho Megersa; Getachew Mulatu; Mohammed Siraj; Gelma Boneya (Veterinary Medicine International)
Foot and mouth disease (FMD) is a highly contagious viral disease of cloven-hoofed animals and one of the endemic diseases in Ethiopia. The study was aimed to estimate the seroprevalence and to assess associated risk factors of foot and mouth disease seroprevalence in West Shewa Zone. A total of 384 sera samples were collected from randomly selected cattle and tested using ELISA for antibodies against nonstructural proteins of foot and mouth disease viruses based on IDEXX FMD Multispecies Ab Test (IDEXX Laboratories Inc, USA). The seroprevalence of foot and mouth disease in West Shewa Zone was found to be 40.4% (95% CI: 35.46–45.27) at an animal and 74.7% (95% CI: 65.58–83.85) at the herd level. Multivariable logistic regression analysis indicated that districts, breed, and animal composition were the potential risk factors of FMD seropositivity. Accordingly, cattle found in Abuna Ginde Beret (odds ratio (OR): 9.1, 95% CI: 2.4–34.1, p=0.001), Cheliya (OR: 8.8, 95% CI: 2.5–31.3, p=0.001), Bako Tibe (OR: 7.6, 95% CI: 2.1–28.3, p=0.002), Tokekutaye (OR: 5.8, 95% CI: 1.7–19.5, p=0.004), and Jeldu (OR: 5.3, 95% CI: 1.3–21.5, p=0.020) districts were more at risk to be infected with FMD than cattle from Ambo. The odds of FMD seropositivity was significantly higher in cattle kept with small ruminants (OR: 2.1, 95% CI: 1.3–3.3, p=0.003) than cattle alone. The analysis also revealed that the odds of seropositivity were 6 times higher in crossbred compared with local cattle (p=0.003). The current study found high seroprevalence of FMD in West Shewa Zone. Therefore, cattle should be vaccinated regularly after the identification of specific FMD serotypes circulating in the study area.